QUICK PERISHABLE FOODSTUFFS AND OPTIMIZATION OF THEIR TRANSPORTATION BY ROAD TRAFFIC AT DISRUPTION TRANSPORT ROAD (Perner's Contacts, 2017)
Each quick perishable foodstuffs must meet their standards on consummation. In the event that they are not met, there is the change to her devalued. The quality of these standards must be ensured, among other things, by the rapid transport of quick perishable foodstuffs. Safe and fast transport of quick perishable foodstuffs is an integral part of road freight transport. This transport requires the fulfilment of the specific conditions laid down in the legislation. The paper focuses on the issue of transport the quick perishable foodstuffs, and in the case of disturbance of the transport network, also on the design of the optimal transport route.
Keywords: security; road; disturbance; food; optimization; transport; perishable; fast; route